Automation and Reshoring : Economic Aspects, Implications on Trade and Labor Market Outcomes - Nguyen, Huu Thinh (2025)
The present dissertation introduces the author’s contribution to the literature on automation and reshoring effects. The work consists of the author’s works focusing on the reshoring channel of automation effects on labor. In particular, article in Chapter 1 by Nguyen (2022, ICFE) presents a review on the interaction between automated robots and reshoring using game-theoretic approach and a case of Adidas‘ Speedfactories. Nguyen, Sharfaei and Soukup (2025, CORA, published in Open Economies Review) present the macroeconomic relevance of robots and reshoring through the channel of international trade. Nguyen and Soukup (2024, EPEAI, under review) build up on the previous research and provide evidence on the automation effects on industrial labor through different reshoring channels. Nguyen and Soukup (2025, ICEE, under review) follow up on the previous macroeconomic findings and study the foreign automation and reshoring effects on labor in Vietnam at the firm-industry level. Moreover, I present various strategies to mitigate negative automation-based reshoring effects for developing countries. Finally, I conclude in the Concluding Remarks section.